Pengelolaan Tanah Wakaf di Lembaga Pendidikan Persepektif Hukum Islam dan Total Quality Management - Ahmadi Ahmadi (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2020)
This study aims to describe the management of waqf land from the perspective of Islamic law. From the standpoint of Islamic law, it was concluded that Nazhir was obliged to manage and develop waqf property according to its purpose, function and designation. Nazir needs to be invited to understand procedures and better management patterns, oriented to the interests of the implementation of Islamic law broadly and in the long term. Techniques that can be applied in total quality management include:: local problem-solving techniques, process measurement techniques, outcome measurement techniques dan consumer-oriented technique. Keywords : Management of waqf land, Islamic Law, Total Quality Management